Positive Politeness Used in the Interviews Conducted by Desi Anwar to Dewi Soekarno and Bill Gates - Arianti, Theresia (JL3T (Journal of Linguistics, Literature and Language Teaching), 2022)
Interview is a popular means of gathering information in our society. However, there is little research on cross-cultural interviews which has been conducted. This research is a descriptive qualitative study which aims to examine Desi Anwar’s choice of positive politeness strategies in relation to her interviewees’ cultural backgrounds, i.e., Dewi Soekarno (Japanese) and Bill Gates (American). The interviews are transcribed and coded based on the positive politeness strategies used and the cultures of Japanese and American communication styles. The instrument used in analyzing the data is Excel Matrix. Findings show that the interview with Dewi Soekarno (Japanese interviewee) contains more positive politeness strategies than the interview with Bill Gates (American interviewee). The positive politeness strategies used in the interview with Dewi Soekarno are Exaggeration, Repetition, Including Both S and H, and also Compliments. This result is contradictory to Japanese and American communication styles, which Japanese do not prefer positive politeness; while Americans do. This study will shade some light on positive politeness used in cross-cultural interviews involving Japanese and American interviewees. Since both interviewees in this research are from different genders, it would be satisfactory if future research includes this aspect into consideration.